Intra-Articular Injection of Human Synovial Membrane-Derived Mesenchymal Stem Cells in Murine Collagen-Induced Arthritis: Assessment of Immunomodulatory Capacity In Vivo - Minglu Yan; Xin Liu; Qiujie Dang; He Huang; Fan Yang; Yang Li (Hindawi Limited, 2017)
The aim of this study was to evaluate the efficacy of human synovial membrane-derived MSCs (SM-MSCs) in murine collagen-induced arthritis (CIA). Male mice (age 7-9 weeks) were injected intra-articularly with SM-MSCs obtained from patients with osteoarthritis, on days 28, 32, and 38 after bovine type II collagen immunization. The efficacy of SM-MSCs in CIA was evaluated clinically and histologically. Cytokine profile analyses were performed by real-time polymerase chain reaction and multiplex analyses. Splenic helper T (Th) cell and regulatory B cell subsets were analyzed by flow cytometry. Intra-articular SM-MSC injection ameliorated the clinical and histological severity of arthritis. Decrease in tumor necrosis factor-α, interferon-γ, and interleukin- (IL-) 17A and increase in IL-10 production were observed after SM-MSC treatment. Flow cytometry showed that Th1 and Th17 cells decreased, whereas Th2, regulatory T (Treg), and PD-1+CXCR5+FoxP3+ follicular Treg cells increased in the spleens of SM-MSC-treated mice. Regulatory B cell analysis showed that CD21hiCD23hi transitional 2 cells, CD23lowCD21hi marginal zone cells, and CD19+CD5+CD1d+IL-10+ regulatory B cells increased following SM-MSC treatment. Our results demonstrated that SM-MSCs injected in inflamed joints in CIA had a therapeutic effect and could prevent arthritis development and suppress immune responses via immunoregulatory cell expansion.